Evaluation of Follow-Up Monitoring Information Systems Using Hot Fit Models (Case Study in Majene District Inspectorate, West Sulawesi) - Angga Anugrawan; Yan Rahadian (Budapest International Research and Critics University, 2022)
This study evaluated the effectiveness of the Follow-up Monitoring Information System (SIPTL) of the Audit Board of the Republic of Indonesia (BPK RI) based on the HOT Fit Model. Evaluation is focused on external SIPTL or from the auditee side. This research is a qualitative research with a case study approach and the object of the research is the Inspectorate of Majene Regency, West Sulawesi. Evaluation is carried out on human aspects (system use and user satisfaction), organization (organizational structure), and technology (quality of systems, information, and services). In the human aspect or Human Resources (HR) management, it shows the suitability of the field of experience, knowledge, and competence. In the organizational aspect, controlling access rights is very good in the form of passwords on each admin and SIPTL inputer. In the technological aspect, the speed of access between pages and the addition of features to the SIPTL application are very easy. Thus, in general, the application of external SIPTL to the Majene District Inspectorate has been effective based on the HOT Fit Model. The disadvantages of SIPTL today are the absence of regular training of users, communication with users that has not run optimally, the absence of regular password changes, and the absence of regular application updates. Further research is recommended to evaluate internal SIPTL, namely from the side of the BPK RI as a user and the addition of research objects as a comparison analysis.